The 2010 World Cup high-frequency data economics: effects on international awareness and (self-defeating) tourism - Stan du Plessis; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
Without a doubt, the 2010 World Cup of soccer in South Africa was a great experience for both soccer fans, who enjoyed a safe and efficiently-run tournament, and their South African hosts. The sporting and social spectacle was broadcast around the world and focused unprecedented media attention on South Africa. Despite the manifest success of the tournament, its short-term effects on international tourism, which are the nucleus of all other short-term positive effects on economic variables such as employment, income and taxes, have turned out to be of a much smaller magnitude than expected or even as reported during the tournament. This may be attributable to self-defeating prophecy effects. This study is a warning against the abuse of economic impact studies, especially those pertaining to major sporting events. It is also a call to use the 'correct' arguments of measurable awareness effects and potential long-term development effects in discussing major sporting events. Methodologically, this study is innovative in its economic analysis of major sporting events because it (i) uses data from social networks and (ii) uses high-frequency daily data on tourism.
Keywords: L83; R53; R58; 330; FIFA World Cup; Mega Sporting Events; Sport Economics; Tourism; South Africa 2010; Selfdefeating prophecies; Awareness; Google; Facebook; Social Networks